2008
DOI: 10.1002/jmv.21094
|View full text |Cite
|
Sign up to set email alerts
|

The effect of early virological response in health‐related quality of life in HCV‐infected patients

Abstract: Twenty-nine HCV-infected patients were treated with pegylated interferon alpha. Diagnosis was based on serum HCV RNA-PCR positive results and liver biopsy. All patients had elevated serum levels of alanine aminotransferase at the time of the study, but liver disease was compensated. Patients were evaluated at baseline treatment and after 4 and 12 weeks of antiviral treatment with the Medical Outcomes Study 36-item Short-Form Health Survey. The Mini-International Neuropsychiatric Interview was used to exclude p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…However, this could be attributed to a reduction in inflammatory activity and even to partial regression of fibrosis and, subsequently, of disease severity, as a recent study showed [28]. Nevertheless, some studies have suggested that HRQOL improves even during antiviral therapy, at early virologic response [7,29], which supports the hypothesis of viral infection itself as the causative factor of HRQOL impairment.…”
Section: Discussionmentioning
confidence: 97%
“…However, this could be attributed to a reduction in inflammatory activity and even to partial regression of fibrosis and, subsequently, of disease severity, as a recent study showed [28]. Nevertheless, some studies have suggested that HRQOL improves even during antiviral therapy, at early virologic response [7,29], which supports the hypothesis of viral infection itself as the causative factor of HRQOL impairment.…”
Section: Discussionmentioning
confidence: 97%
“…Various studies have shown that HRQoL improves after SVR has been achieved [14,15,17–19]. A recent study of HRQoL in 29 patients receiving PEG‐IFN‐α showed that the 13 patients who achieved SVR after 12 weeks of treatment had significantly improved mental health summary scores on the SF‐36 [14].…”
Section: Does Sustained Viral Response Lead To Improved Hrqol?mentioning
confidence: 99%
“…This has been associated with improvement in health-related quality of life; hepatic histological features; and even a reduction in long-term outcomes such as cirrhosis, hepatocellular carcinoma, and mortality [1][2][3][4]. Currently, the recommended antiviral treatment for HCV is a combination of pegylated-interferon (PEG-INF) and ribavirin.…”
Section: Introductionmentioning
confidence: 98%